Plano de negócio – um estudo de caso de uma empresa familiar, gaúcha, fabricante de componentes para calçados no Vale dos Sinos, que está em processo de expansão - Fogaça, Leonel José (Universidade do Vale do Rio dos Sinos, 2014)
In family firms the decision-making process is often based only on the experiences of the manager as well as his entrepreneurial spirit without having a support structure that assists in risk measurement. The business plan is a management tool of fundamental importance, the ability to illustrate the ideas of the entrepreneur and assess the risks involved in an investment project. This study aims to assess the feasibility of a project to expand a company's footwear components sector, located in the valley region of the bells in waterfront, through a business plan. Using a business plan possible to develop a strategic plan and evaluate the economic viability of the investment, as well as test their sensitivity to the risks involved. This research adopted the strategy of the case study with exploratory and qualitative approach. For data collection interview techniques, direct observation and document analysis were used. As a result the business plan clarified the strategic planning of the company and found their economic viability. However possible to demonstrate that the project is sensitive to simulated adversity, concluding that despite the manager having correctly decided by the option to invest, perhaps unaware of the fragility against the risks involved in the business.
Keywords: Plano de negócio; Empresa familiar; Análise de investimento; Planejamento estratégico; Business plan; Family business; Investment analysis; Strategic planning